A PTFE electromagnetic shielding material and its preparation method and application
By adopting a three-layer sandwich structure PTFE electromagnetic shielding material, combined with the polytetrafluoroethylene conductive microporous membrane layer and the conductive layer, the shortcomings of existing materials in terms of flexibility, smooth surface and continuous conductivity are solved, and efficient electromagnetic shielding performance is achieved.
Patent Information
- Application Number
- CN202411756054.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The existing electromagnetic shielding materials have shortcomings in their flexibility, smooth and smooth surface and continuous conductivity, resulting in defects in sealing performance and shielding performance.
The PTFE electromagnetic shielding material adopts a three-layer sandwich structure, including the upper and lower polytetrafluoroethylene conductive microporous film layer and the middle conductive layer, improves the mechanical properties and conductivity of the material by adding reinforcement materials and conductive materials to the conductive microporous film layer and adding thermoplastic resin to the conductive layer.
The flexibility, sealing and mechanical strength of the material are improved, and at the same time, it has good conductivity and shielding performance, with shielding performance reaching ≥80db.
Smart Images

Figure CN119233617B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electromagnetic shielding, and specifically relates to a PTFE electromagnetic shielding material and a preparation method and application thereof. Background Art
[0002] Electronic equipment such as radars, instruments and computers are usually sealed in shielded enclosures because electromagnetic energy in the radio frequency range can interfere with them. An effectively sealed and shielded enclosure can prevent the electromagnetic energy inside from accidentally leaking out, thereby interfering with the normal operation of electromagnetic sensitive electronic equipment outside, and conversely prevent the electromagnetic energy outside from accidentally entering and affecting its normal operation. However, shielded enclosures are not perfect due to input and output connections, breaks, etc. Therefore, electromagnetic shielding materials with sealing properties and shielding effectiveness came into being.
[0003] A widely used EMI shielding material is a silicone elastomer filled with conductive particles, which has been used as a conductive gasket to reduce EMI and RFI. However, such materials tend to be relatively hard (e.g., Shore A hardness of about 60 or higher), resulting in their inability to deform under low pressure. In addition, it is not easy to be stamped into a thin gasket, so its sealing performance has certain defects. Some subsequent EMI shielding materials may deform under less pressure, but these gaskets do not have continuous conductivity throughout the material.
[0004] Another existing electromagnetic shielding material is to coat an insulating layer on a carrier film, dry the surface of the insulating layer and wait for hardening, and then select to process a metal layer on the outside of the insulating layer to make a semi-finished product according to actual needs, and coat the outside of the semi-finished product with conductive layer glue, usually the thickness of the conductive layer is 5-15um, and finally the protective film is attached to the outside of the conductive layer to make an electromagnetic shielding film. In order to enable the electromagnetic shielding film to obtain relatively excellent conductivity and shielding effectiveness, the conductive particles of the conductive layer are selected to be branch-shaped, flaky or spherical conductive powders with larger particle sizes, usually the particle size of the conductive powder is 5-20um. Due to the large particle size, the adhesion between the conductive particles is increased, so that the conductive performance and shielding effectiveness of the electromagnetic shielding film are good. However, since the particle size of the conductive particles is relatively large when the conductive layer is coated, when the conductive layer is coated with a thickness of 5-15um, the larger particle size makes the appearance of the conductive layer rough and uneven. In order to improve the roughness and unevenness of the appearance of the conductive layer, the method of increasing the thickness of the conductive layer is usually adopted to improve it, but the increase in the thickness of the conductive layer will cause an increase in cost. If the roughness and unevenness of the conductive layer's appearance is improved by reducing the particle size of the conductive particles, the mutual adhesion of the conductive particles is reduced due to the reduction in the particle size of the conductive particles, which in turn affects the conductivity and shielding effectiveness of the conductive layer.
[0005] Therefore, designing an electromagnetic shielding material with excellent electromagnetic shielding performance, flexibility, smooth surface and continuous conductivity has become a technical problem that needs to be urgently solved in the existing technology. Summary of the invention
[0006] In order to solve the drawbacks of the above-mentioned prior art, the present invention provides a continuous conductive flexible polytetrafluoroethylene product, which has a smooth surface and high mechanical properties. It has excellent performance of PTFE and has excellent effective electromagnetic shielding properties in the entire radio frequency and electromagnetic energy spectrum. The specific technical solution is as follows:
[0007] A PTFE electromagnetic shielding material, the PTFE electromagnetic shielding material is a three-layer sandwich structure, the upper layer and the lower layer are both polytetrafluoroethylene conductive microporous membrane layers, the middle layer is a conductive layer,
[0008] The polytetrafluoroethylene conductive microporous membrane layer comprises PTFE resin, reinforcing material and conductive material, and the conductive layer comprises thermoplastic resin and conductive material.
[0009] The density of the PTFE electromagnetic shielding material is 0.55-0.80 g / cm 3 , strength ≥25MPa, elongation at break ≥290%, volume resistivity ≤0.015Ω.cm, shielding effectiveness ≥80db.
[0010] Furthermore, the PTFE resin is a dispersed resin or a modified dispersed resin having an SSG of less than 2.140 and an extrusion pressure greater than 50 MPa at a compression ratio of RR400, and the modifier monomer of the modified dispersed resin is one or a combination of perfluorohexylethylene, chlorotrifluoroethylene, perfluoromethyl vinyl ether, perfluoropropyl vinyl ether, perfluorobutylethylene and hexafluoropropylene.
[0011] Furthermore, the reinforcing material is any one of polychlorotrifluoroethylene (PCTFE), PVDF, ETFE, PFA and FEP.
[0012] Furthermore, the conductive material is one or more of carbon fiber, graphite, acetylene black and metal. Preferably, the conductive material is graphite.
[0013] Furthermore, the thermoplastic resin is any one of PFA, FEP and PTFE powder.
[0014] The present invention also discloses a method for preparing any of the above-mentioned PTFE electromagnetic shielding materials, comprising the following steps:
[0015] 1) Preparation of PTFE conductive microporous membrane layer:
[0016] Add reinforcing material and conductive material to PTFE resin to prepare a mixture, add auxiliary agent and fully mix, sieve, mature, make preform and then extrude, calender, deoil, stretch below the reinforcing material melting point, then shrink the film below the PTFE resin melting point above the reinforcing material melting point to obtain the PTFE conductive microporous membrane layer. The shrinking process of the conductive microporous membrane greatly plays a role in fixing the conductive particles. Preferably, the membrane is shrunk by the differential rotation of the stretching roller. The preparation method of the PTFE conductive microporous membrane layer of the present invention not only fixes the conductive particles to prevent them from falling off, but also enhances the strength of the membrane to a certain extent. Wherein, the auxiliary agent is aviation kerosene or naphtha, preferably isopar G, isopar M, isopar V in aviation kerosene, more preferably isopar M, and the addition amount of the auxiliary agent is 20~30wt% of the PTFE resin in the mixture.
[0017] 2) Preparation of PTFE electromagnetic shielding materials:
[0018] The conductive material containing thermoplastic resin is applied to the PTFE conductive microporous membrane layer prepared in step 1) by dry method to prepare a conductive layer, and the PTFE conductive microporous membrane layer is attached to the other side of the conductive layer, and hot pressed to prepare the PTFE electromagnetic shielding material.
[0019] Furthermore, in step 1), the PTFE resin accounts for 60-80wt% of the mixture, the reinforcing material accounts for 5-15wt%, and the conductive material accounts for 15-35wt%. Too little conductive material will make it difficult to conduct electricity, and too much conductive material will easily fall off.
[0020] Furthermore, in step 2), the conductive material containing the thermoplastic resin accounts for 40-90wt%. If the conductive material accounts for a small proportion, the conductivity will be affected and the shielding effectiveness will not be improved. If the conductive material accounts for too much, the conductive layer will become thicker, and the thermoplastic resin will not be able to fix the conductive material and increase the interlayer adhesion.
[0021] Furthermore, in step 1), the aging temperature is 35-55°C.
[0022] Furthermore, the deoiling temperature and the stretching temperature are both 160°C to below the melting point of the reinforcing material, and the stretching temperature is higher than the deoiling temperature to ensure that there is no film stretching during deoiling.
[0023] Furthermore, the shrinkage temperature of the film is equal to or higher than the melting point of the reinforcing material and lower than the melting point of the PTFE resin.
[0024] Furthermore, in step 1), the stretching ratio is 2 to 5 times.
[0025] Furthermore, in step 1), the speed ratio of the stretching rollers is 1:0.85-0.95. If the ratio is greater than 0.95, the conductive particles cannot be fixed well, and color stripes appear on the film; if the ratio is less than 0.85, the contraction forces of the nodes and fibers at different positions of the film are different, which will make the film thickness uneven and the film surface wrinkled, thereby affecting the electromagnetic shielding performance.
[0026] Furthermore, in step 1), the mixing of PTFE resin, reinforcing material and conductive material can be dispersion coagulation or dry material blending. If dry material blending, the reinforcing material and conductive material should be blended first, and then blended with PTFE resin.
[0027] The present invention also discloses the application of any of the above-mentioned PTFE electromagnetic shielding materials in the field of electromagnetic shielding. For example, the PTFE electromagnetic shielding materials can be used to prepare shielding shells of electronic equipment such as radars, instruments and meters, and computers.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The PTFE shielding material of the present invention has good softness, sealing and mechanical strength because it adopts polytetrafluoroethylene conductive microporous membrane, and also has the excellent properties of polytetrafluoroethylene itself, such as acid and alkali resistance and high temperature resistance.
[0030] (2) Reinforcement materials are added to the PTFE conductive microporous membrane layer to improve the wear resistance and mechanical properties of the shielding material, preventing accidental breakage or rupture during use. On the other hand, it also plays a role in the adhesion of the conductive particles in the microporous membrane layer and the conductive layer to a certain extent.
[0031] (3) The three-layer sandwich structure greatly increases the amount of conductive material added and is not easy to fall off or leak. The addition of thermoplastic resin also improves the bonding strength between the layers. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a SEM image of the PTFE conductive microporous membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The technical scheme in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Unless otherwise specified, the raw materials used in the present invention are all common commercial products, and the processing methods used are all conventional methods in the art unless otherwise specified.
[0034] In the embodiments and comparative examples, the performance test method of the polytetrafluoroethylene shielding material is as follows:
[0035] 1. Determination of tensile strength and elongation at break: The tensile strength of polytetrafluoroethylene shielding materials is tested according to GB / T1040-92, with three groups of samples per test and the average value taken.
[0036] 2. Density determination: Cut samples of about 50 mm in length and 50 mm in width from the sheets of the examples / comparative examples, and measure and record the length, width, thickness and mass of each sample. The density of the sample is determined by the following calculation:
[0037] Density (g / cm 3 ) = mass (g) / volume (cm 3 )
[0038] Among them, volume (cm 3 ) = length (cm) x width (cm) x thickness (cm).
[0039] 3. Volume resistivity: The use area is 6.45cm 2 The volume resistivity is measured with a circular silver probe. A 0.5 kg weight is placed on the probe to obtain the resistance of the sample at 7 MPa. The conversion between resistance and volume resistivity is as follows:
[0040] ρ=RA / L(Ω·cm)
[0041] ρ = volume resistivity, R = resistance (Ω), A = sample area (cm 2 ), L = sample thickness (cm).
[0042] 4. Shielding effectiveness: The electromagnetic shielding effectiveness is tested according to GJB8820-2015, with three groups of samples for each test and the average value taken. Shielding effectiveness = 20log(T), where T = transmission coefficient; T = V0 / V1, where V0 = receiving voltage without shielding material (v); V1 = receiving voltage with shielding material (v). The electromagnetic shielding effectiveness is tested at 100kHZ-40GHZ.
[0043] Example 1
[0044] This embodiment discloses a method for preparing a PTFE electromagnetic shielding material:
[0045] 1) Preparation of PTFE conductive microporous membrane layer:
[0046] 70wt% of unmodified PTFE resin (SSG is 2.135, RR400 extrusion pressure is 51MPa), 10wt% of PVDF, and 20wt% of conductive graphite are mixed to prepare a mixture, and the additive isopar M accounting for 28wt% of the unmodified PTFE resin is added. After being fully mixed on a three-dimensional mixer, it is sieved with a sieve with an aperture of 1.44mm, placed at 35℃ for aging, and then extruded and calendered to make a preform, deoiled at 160℃, and then stretched 3 times at 170℃, and shrunk at 250℃ by differential rotation of the stretching roller, with a shrinkage ratio of 1:0.90. In order to allow the completely molten reinforcing material to fix the conductive particles to prevent them from falling off, and to enhance the strength of the membrane to a certain extent.
[0047] 2) Preparation of PTFE electromagnetic shielding materials:
[0048] A PFA resin mixture containing 90 wt% of graphite is dry-applied to the PTFE conductive microporous membrane layer prepared in step 1) to form a conductive layer, and the PTFE conductive microporous membrane layer is further attached to the other side of the conductive layer, and finally hot-pressed to form a three-layer sandwich structure PTFE electromagnetic shielding material with PTFE conductive microporous membrane layers on the upper and lower layers and a conductive layer in the middle.
[0049] Example 2
[0050] (1) Preparation of PTFE conductive microporous membrane layer:
[0051] 60wt% of unmodified PTFE resin (SSG is 2.138, RR400 extrusion pressure is 52MPa), 15wt% of ETFE, and 25wt% of conductive graphite are mixed to prepare a mixture, and the additive isopar M accounting for 28wt% of the unmodified PTFE resin is added. After being fully mixed on a three-dimensional mixer, the mixture is sieved with a sieve with an aperture of 1.44mm, aged at 50°C, extruded into a preform, calendered, deoiled at 200°C, and then stretched 4 times at 250°C, and shrunk by differential rotation of stretching rollers at 300°C, with a shrinkage ratio of 1:0.95.
[0052] (2) Preparation of PTFE electromagnetic shielding materials:
[0053] A FEP resin mixture containing 70wt% graphite is dry-applied to the PTFE conductive microporous membrane layer prepared in step 1) to form a conductive layer, and the PTFE conductive microporous membrane layer is further attached to the other side of the conductive layer, and finally hot-pressed to form a three-layer sandwich structure PTFE electromagnetic shielding material with PTFE conductive microporous membrane layers on the upper and lower layers and a conductive layer in the middle.
[0054] Example 3
[0055] (1) Preparation of PTFE conductive microporous membrane layer:
[0056] 80wt% of modified PTFE resin (SSG is 2.135, RR400 extrusion pressure is 51Mpa, and the modifier monomer is perfluoropropyl vinyl ether), 5wt% of PFA, and 15wt% of conductive graphite are mixed to prepare a mixture, and the auxiliary agent isopar M accounting for 28wt% of the modified PTFE resin is added. After being fully mixed on a three-dimensional mixer, the mixture is sieved with a sieve with an aperture of 1.44mm, aged at 40°C, extruded into a preform, calendered, deoiled at 180°C, and then stretched 5 times at 200°C, and shrunk by differential rotation of stretching rollers at 280°C, and the shrinkage ratio is 1:0.85.
[0057] (2) Preparation of PTFE electromagnetic shielding materials:
[0058] A PFA resin mixture containing 60 wt% graphite is dry-applied to the PTFE conductive microporous membrane layer prepared in step 1) to form a conductive layer, and the PTFE conductive microporous membrane layer is further attached to the other side of the conductive layer, and finally hot-pressed to form a three-layer sandwich structure PTFE electromagnetic shielding material with the upper and lower layers being PTFE conductive microporous membrane layers and the middle layer being a conductive layer.
[0059] Example 4
[0060] (1) Preparation of PTFE conductive microporous membrane layer:
[0061] 60wt% of modified PTFE resin (SSG is 2.135, RR400 extrusion pressure is 51Mpa, and modifier monomer is hexafluoropropylene), 5wt% of PVDF, and 35wt% of conductive graphite are mixed to prepare a mixture, and an auxiliary agent isopar M accounting for 28wt% of the modified PTFE resin is added. After being fully mixed on a three-dimensional mixer, the mixture is sieved with a sieve with an aperture of 1.44mm, aged at 40°C, extruded into a preform, calendered, deoiled at 160°C, and then stretched by 2 times at 170°C, and shrunk by differential rotation of stretching rollers at 280°C, with a shrinkage ratio of 1:0.85.
[0062] (2) Preparation of PTFE electromagnetic shielding materials:
[0063] A PTFE micropowder resin mixture containing 40wt% graphite is dry-applied to the PTFE conductive microporous membrane layer prepared in step 1) to form a conductive layer, and the PTFE conductive microporous membrane layer is further attached to the other side of the conductive layer, and finally hot-pressed to form a three-layer sandwich structure PTFE electromagnetic shielding material with PTFE conductive microporous membrane layers on the upper and lower layers and a conductive layer in the middle.
[0064] Example 5
[0065] (1) Preparation of PTFE conductive microporous membrane layer:
[0066] 75wt% of modified PTFE resin (SSG is 2.135, RR400 extrusion pressure is 51MPa, and modifier monomer is chlorotrifluoroethylene), 10wt% of PFA, and 15wt% of conductive graphite are mixed to prepare a mixture, and an auxiliary agent isopar M accounting for 28wt% of the modified PTFE resin is added. After being fully mixed on a three-dimensional mixer, the mixture is sieved with a sieve with an aperture of 1.44mm, aged at 35°C, extruded into a preform, calendered, deoiled at 250°C, and then stretched 4 times at 280°C, and shrunk by differential rotation of stretching rollers at 315°C, with a shrinkage ratio of 1:0.87.
[0067] (2) Preparation of PTFE electromagnetic shielding materials:
[0068] A PFA resin mixture containing 80 wt% graphite is dry-applied to the PTFE conductive microporous membrane layer prepared in step 1) to form a conductive layer, and the PTFE conductive microporous membrane layer is further attached to the other side of the conductive layer, and finally hot-pressed to form a three-layer sandwich structure PTFE electromagnetic shielding material with PTFE conductive microporous membrane layers on the upper and lower layers and a conductive layer in the middle.
[0069] Comparative Example 1
[0070] Compared with Example 1, the difference is that no reinforcing material is added, and other preparation conditions are the same as those of Example 1.
[0071] Comparative Example 2
[0072] Compared with Example 1, the difference is that the added amount of the reinforcing material is 20%, and the other preparation conditions are the same as those of Example 1.
[0073] Comparative Example 3
[0074] Compared with Example 1, the difference is that the shrinkage temperature of the film is 165°C, which is lower than the melting point of the reinforcing material, and the other preparation conditions are the same as those of Example 1.
[0075] Comparative Example 4
[0076] Compared with Example 1, the difference is that the shrinkage temperature of the film is 350°C, which is higher than the melting point of the PTFE resin, and the other preparation conditions are the same as those of Example 1.
[0077] Comparative Example 5
[0078] Compared with Example 1, the difference is that the differential speed ratio of the stretching rollers during shrinkage of the film is 1:0.96, and the other preparation conditions are the same as those of Example 1.
[0079] Comparative Example 6
[0080] Compared with Example 1, the difference is that the differential speed ratio of the stretching rollers during shrinkage of the film is 1:0.80, and the other preparation conditions are the same as those of Example 1.
[0081] Comparative Example 7
[0082] Compared with Example 1, the difference is that a single-layer PTFE conductive microporous membrane is used instead of a three-layer sandwich structure. That is, only step 1) is used to prepare the PTFE conductive microporous membrane, and step 2) is not performed.
[0083] Comparative Example 8
[0084] Compared with Example 1, the difference is that the content of the conductive material in the conductive layer is 35 wt %, and the other preparation conditions are the same as those in Example 1.
[0085] Comparative Example 9
[0086] Compared with Example 1, the difference is that the content of the conductive material in the conductive layer is 95wt%, and the other preparation conditions are the same as those in Example 1.
[0087] Comparative Example 10
[0088] Compared with Example 1, the PTFE resin selected is a PTFE dispersed resin with an SSG of 2.220 and an RR400 extrusion pressure of 32 MPa.
[0089] The properties of the PTFE electromagnetic shielding materials or PTFE conductive microporous membranes prepared in Examples 1 to 5 and Comparative Examples 1 to 10 were tested. The test results are shown in Table 1.
[0090] Table 1 Relevant performance indicators of PTFE electromagnetic shielding materials or PTFE conductive microporous membranes obtained in various embodiments and comparative examples.
[0091]
[0092] Referring to Table 1, it can be seen from the test results of Examples 1 to 5 and Comparative Examples 1 to 10 that the comprehensive performance of the PTFE electromagnetic shielding materials prepared by the preparation method of the present invention is better.
[0093] It can be seen from the test results of Example 1 and Comparative Example 1 that without adding reinforcing material, the mechanical properties of the PTFE electromagnetic shielding material are significantly reduced.
[0094] It can be seen from the test results of Example 1 and Comparative Example 2 that when the addition amount of the reinforcing material is 20%, the membrane surface becomes flowery. This is simply because the reinforcing material does not have fibrous properties. Too much addition will affect the tensile properties and uniformity of the membrane surface of the microporous membrane.
[0095] It can be seen from the test results of Example 1 and Comparative Example 3 that when the shrinkage temperature of the membrane is lower than the melting point of the reinforcing material, the reinforcing material cannot reach a molten state and cannot play a role in enhancing the mechanical properties of the PTFE conductive microporous membrane and fixing the conductive particles.
[0096] It can be seen from the test results of Example 1 and Comparative Example 4 that when the shrinkage temperature of the membrane is higher than the melting point of the PTFE resin, the nodes melt and the fibers cannot shrink, so the fibers or even the membrane break during the shrinkage process.
[0097] From the test results of Example 1 and Comparative Example 5, it can be seen that when the differential speed ratio of the stretching rollers during the shrinkage of the film is 1:0.96, the shrinkage degree of the nodes and fibers is small, which cannot play a good role in fixing the conductive particles, and it is found that the color stripes on the surface of the film are obvious.
[0098] It can be seen from the test results of Example 1 and Comparative Example 6 that when the differential speed ratio of the stretching rollers during the shrinkage of the membrane is 1:0.80, the differential speed ratio of the stretching rollers is large, and the shrinkage forces of the nodes and fibers at different positions of the membrane are different, which will make the thickness of the membrane uneven and the membrane surface wrinkled, thereby affecting the electromagnetic shielding effectiveness.
[0099] It can be seen from the test results of Example 1 and Comparative Example 7 that the electromagnetic shielding effectiveness of the single-layer PTFE conductive microporous membrane is significantly reduced due to the low filling amount of conductive particles.
[0100] From the test results of Example 1 and Comparative Example 8, it can be seen that the content of conductive material is low, the content of thermoplastic resin is high, and the porosity is greatly reduced, resulting in an increase in volume resistivity and a slight decrease in shielding effectiveness.
[0101] It can be seen from the test results of Example 1 and Comparative Example 9 that the content of the conductive material is too high and the content of the thermoplastic resin is too low, which cannot play the role of fixing the conductive material and increasing the interlayer adhesion.
[0102] It can be seen from the test results of Example 1 and Comparative Example 10 that when the fibers of the PTFE dispersed resin are long, the formation of the conductive network is affected, so that the volume resistivity increases and the shielding effectiveness decreases.
[0103] Figure 1 The SEM image of the PTFE conductive microporous membrane prepared in Example 1 is shown in FIG. Figure 1 It can be seen that the conductive particles are firmly fixed and contact each other to form a conductive network.
Claims
1. A method for preparing a PTFE electromagnetic shielding material, characterized in that: The steps include: 1) Preparation of PTFE conductive microporous membrane layer: Adding reinforcing material and conductive material to PTFE resin to prepare a mixture, adding auxiliary agent and fully mixing, screening, ripening, making a preform, extruding, calendering, deoiling, stretching below the melting point of reinforcing material, and then shrinking the membrane above the melting point of reinforcing material and below the melting point of PTFE resin to obtain PTFE conductive microporous membrane layer; 2) Preparation of PTFE electromagnetic shielding materials: Applying a conductive material containing a thermoplastic resin to the PTFE conductive microporous membrane layer prepared in step 1) by a dry method to prepare a conductive layer, attaching the PTFE conductive microporous membrane layer to the other side of the conductive layer, and hot pressing to prepare a PTFE electromagnetic shielding material; Wherein, in step 1), the PTFE resin in the mixture accounts for 60-80wt%, the reinforcing material accounts for 5-15wt%, and the conductive material accounts for 15-35wt%.
2. The method for preparing the PTFE electromagnetic shielding material according to claim 1, characterized in that: In step 2), the conductive material contains a thermoplastic resin, and the conductive material accounts for 40-90wt%.
3. The method for preparing the PTFE electromagnetic shielding material according to claim 1, characterized in that: In step 1), the aging temperature is 35-55°C.
4. The method for preparing the PTFE electromagnetic shielding material according to claim 1, characterized in that: In step 1), the deoiling temperature and the stretching temperature are both 160° C. to below the melting point of the reinforcing material, and the stretching temperature is higher than the deoiling temperature.
5. The method for preparing the PTFE electromagnetic shielding material according to claim 1, characterized in that: In step 1), the stretching ratio is 2 to 5 times.
6. The method for preparing the PTFE electromagnetic shielding material according to claim 1, characterized in that: In step 1), the film is shrunk by differential rotation of the stretching rollers, and the differential speed ratio of the stretching rollers is 1:0.85-0.
95.
7. A PTFE electromagnetic shielding material prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The PTFE electromagnetic shielding material is a three-layer sandwich structure, the upper and lower layers are both polytetrafluoroethylene conductive microporous membrane layers, and the middle layer is a conductive layer. The polytetrafluoroethylene conductive microporous membrane layer comprises PTFE resin, reinforcing material and conductive material, and the conductive layer comprises thermoplastic resin and conductive material. The density of the PTFE electromagnetic shielding material is 0.55-0.80 g / cm 3 , strength ≥25MPa, elongation at break ≥290%, volume resistivity ≤0.015Ω.cm, shielding effectiveness ≥80db.
8. The PTFE electromagnetic shielding material according to claim 7, characterized in that: The PTFE resin is a dispersed resin or a modified dispersed resin with an SSG of less than 2.140 and an extrusion pressure greater than 50 MPa at a compression ratio of RR400. The modifier monomer of the modified dispersed resin is one or a combination of perfluorohexylethylene, chlorotrifluoroethylene, perfluoromethyl vinyl ether, perfluoropropyl vinyl ether, perfluorobutylethylene and hexafluoropropylene.
9. The PTFE electromagnetic shielding material according to claim 7, characterized in that: The reinforcing material is any one of PCTFE, PVDF, ETFE, PFA and FEP; And / or, the conductive material is one or more of carbon fiber, graphite, acetylene black and metal; And / or, the thermoplastic resin is any one of PFA, FEP and PTFE powder.
10. Use of the PTFE electromagnetic shielding material according to any one of claims 7 to 9 in the field of electromagnetic shielding.
Citation Information
Patent Citations
Polytetrafluoroethylene porous material and process for production of the same
US5688836A
Self-healing electromagnetic shielding material, preparation method therefor and application thereof
WO2023060739A1